Human 5' --> 3' exonuclease Xrn2 promotes transcription termination at co-transcriptional cleavage sites. - West, S; Gromak, N; Proudfoot, N (2004)
Eukaryotic protein-encoding genes possess poly(A) signals that define the end of the messenger RNA and mediate downstream transcriptional termination by RNA polymerase II (Pol II). Termination could occur through an 'anti-termination' mechanism whereby elongation factors dissociate when the poly(A) signal is encountered, producing termination-competent Pol II. An alternative 'torpedo' model postulated that poly(A) site cleavage provides an unprotected RNA 5' end that is degraded by 5' --> 3' exonuclease activities (torpedoes) and so induces dissociation of Pol II from the DNA template. This model has been questioned because unprocessed transcripts read all the way to the site of transcriptional termination before upstream polyadenylation. However, nascent transcripts located 1 kilobase downstream of the human beta-globin gene poly(A) signal are associated with a co-transcriptional cleavage (CoTC) activity that acts with the poly(A) signal to elicit efficient transcriptional termination. The CoTC sequence is an autocatalytic RNA structure that undergoes rapid self-cleavage. Here we show that CoTC acts as a precursor to termination by presenting a free RNA 5' end that is recognized by the human 5' --> 3' exonuclease Xrn2. Degradation of the downstream cleavage product by Xrn2 results in transcriptional termination, as envisaged in the torpedo model.